Bröllopskoordinatorn som ceremonimästare - Salomonsson, Karin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
The growing interest in the ’white and lavish’ wedding is not to be mistaken. It can be seen in the expanding bridal industry, with its special magazines, bridal shows, internet pages and vast number of products and services for the ’perfect wedding’. To be able to navigate this market a relatively new service has been imported from the USA, the wedding planner. Through interviews, this article explores the ways in which the wedding planner describes his or her work, contact with clients, and what they see as their main task — staging dreams, creating a ’personal’ wedding and providing security. What role do the wedding planner play as trendsetter and/or defender of ritual norms?